2022
DOI: 10.3389/fmolb.2022.966754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the immunogenicity of heparin and heparin derivatives by measuring their binding to platelet factor 4 using biolayer interferometry

Abstract: Heparin (HP) is a polysaccharide that is widely used in the clinic as an anticoagulant. A major side effect associated with HP is the heparin-induced thrombocytopenia (HIT), which is initiated by the immune response to complex formed by HP and platelet factor 4 (PF4). Low molecular weight heparins (LMWHs) are the depolymerized version of HP, which have reduced risks of inducing HIT. However, it is still necessary to evaluate the immunogenicity of LMWHs to ensure their drug safety. Since HIT involves very compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Resulting binding curves were fit globally using non-linear regression to determine binding kinetics for association and dissociation (Supplementary Table S4). (Shah and Duncan, 2014;Chen et al, 2022). The equilibrium dissociation constant (K D ) of FGF-2 binding with Hep Multi (~1.6 nM) matched well with previous literature values (Zhang et al, 2019) while that of Hep Single was found to be significantly lower (~0.97 nM), indicating higher affinity binding between the Hep Single and FGF-2 (Figure 3C).…”
Section: Resultssupporting
confidence: 89%
“…Resulting binding curves were fit globally using non-linear regression to determine binding kinetics for association and dissociation (Supplementary Table S4). (Shah and Duncan, 2014;Chen et al, 2022). The equilibrium dissociation constant (K D ) of FGF-2 binding with Hep Multi (~1.6 nM) matched well with previous literature values (Zhang et al, 2019) while that of Hep Single was found to be significantly lower (~0.97 nM), indicating higher affinity binding between the Hep Single and FGF-2 (Figure 3C).…”
Section: Resultssupporting
confidence: 89%
“…[86,[226][227][228] For Hep and HS, chemical treatments have been developed to achieve specific 2-O, 6-O, or N-desulfation and are now commonly used. [223,[229][230][231][232][233][234] N-desulfation is typically carried out through solvolytic desulfation with dimethyl sulfoxide (DMSO) containing methanol, without depolymerization of HS chains and minimal O-desulfation. [235] Specific 2-O desulfation is generally achieved using sodium hydroxide treatment.…”
Section: Specific Desulfationmentioning
confidence: 99%